New achievements on relaxation dynamics of atoms and molecules photoexcited in the tender x-ray domain at synchrotron SOLEIL. (20th January 2017) - Piancastelli, M N; Guillemin, R; Marchenko, T; Journel, L; Travnikova, O; Marin, T; Goldsztejn, G; de Miranda, B Cunha; Ismail, I; Simon, M
Abstract: The so-called 'tender' x-ray domain, from 2 to 13 keV, has recently become available for atomic and molecular studies at the French synchrotron SOLEIL with state-of-the-art photon and electron energy resolution. We investigated a wealth of new phenomena by means of photoelectron and Auger spectroscopy and electron–ion coincidence techniques. The list includes recoil due to the photoelectron's momentum, ultrafast nuclear motion on the femto- and sub-femtosecond time scale, double-core-hole studies, electron recapture effects, exotic Auger decay pathways, deep-edge molecular-frame photoelectron angular distribution studies, and core-hole localization/delocalization phenomena for deep-core vacancies. We demonstrate that the newly accessible extended photon energy range does not simply allow studying more systems with deeper core edges, but opens a totally new horizon in what concerns electron and nuclear dynamics of deep-core-excited and core-ionized isolated species.